An investigation of consumers' purchase intentions towards omni-channel shopping: A qualitative exploratory study. Issue 10 (25th October 2018) - Kazancoglu, Ipek; Aydin, Hatice
Abstract : Purpose: The growth of omni-channel retailing is causing consumers to change their habits and shopping behaviour. It is essential to understand the factors on purchase intention within the consumer context. The purpose of this paper is to explore factors that are influencing consumers to use omni-channel in their shopping behaviour – specifically in the apparel sector in Turkey as an emerging country. Design/methodology/approach: Designed as exploratory research, this study used four different focus groups. Focus groups were conducted with university students who have experienced the company's omni-channel applications. The study sample included a total of 30 purposefully selected university students in Izmir, Turkey, who previously shopped at the same store. The selected retail store is the leading domestic shopping brand and the pioneer in omni-channel in the apparel and fashion sector in Turkey. The participants were given three company-related scenarios which were used to help the students to better understand omni-channel applications of the company. Then, they were asked to discuss their perceptions and intentions towards omni-channel shopping. Content analysis was used for analysing transcripts. Findings: The findings of the focus groups have revealed 12 themes about the intentions of the university students towards omni-channel shopping. Among 12 themes, it is observed that 6 of them have similarities with the variables of the UTAUT2 model. The findings of the study showed that, beside the additional themes, the predetermined variables of the UTAUT2 model within the literature; which are "performance expectancy", "effort expectancy", "facilitating conditions", "hedonic motivation", "habit" and "price value" have affected purchasing intentions towards omni-channel shopping. This study proposed six additional themes which were not revealed in the previous studies on purchase intentions in an omni-channel shopping in apparel sector. The six additional themes proposed in this study are; "perceived trust", "situational factors", "perceived risk", "anxiety", "need for interaction" and "privacy concern". Research limitations/implications: This study is limited to the focus group interviews held in only one university with students from the same programme. The findings are obtained also only valid for the relevant retail store and city, and cannot yet be generalised. Practical implications: The relationships suggested in this exploratory study can further be analysed by quantitative study. It is also claimed that the findings of this study can act as a framework to extend the UTAUT2 model by integrating perceived trust, situational factors, perceived risk, anxiety, need for interaction and privacy concern. This model will enable retailers to understand consumer expectations towards omni-channel shopping and to focus on integrating these factors through whole purchasing process in order to increase omni-channel sales. Originality/value: The literature on omni-channel has concentrated on the retailers' perspective, whereas this study aims to reveal an insight from the consumer perspective. The contribution of the study is to provide a framework for understanding the themes on consumer viewpoint in the omni-channel shopping behaviour.